Selection of indigenous rhizobia to the cowpea; pigeonpea and jackbean crops in the coastal tableland of Sergipe; Brazil - Fernandes, Marcelo Ferreira; Fernandes, Roberta Pereira Miranda; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 2003)
The inoculation of rhizobial strains in jackbean (Canavalia ensiformis), cowpea (Vigna unguiculata) and pigeonpea (Cajanus cajan), recommended for other regions of Brazil, has not resulted in increases of biological nitrogen fixation rates and plant growth in soils of the coastal tableland of Sergipe (Brazilian Northeast). The objectives of this work were to evaluate the symbiotic effectiveness of indigenous rhizobia from that coastal tableland associated to these three legumes and their tolerance to stresses. Seventeen rhizobia strains were isolated and evaluated in a greenhouse. Four strains were selected for pigeonpea; seven for cowpea and three for jackbean. Nodules number and dry weight were related to shoot dry weight, leaf area and leaf N content, in all three legumes. The same strains were efficient for both cowpea and pigeonpea. Three pigeonpea (R35, R43 and R45) and two cowpea (R10 and R17) rhizobia were characterized in vitro and all showed tolerance to high levels of nalidix acid, chloramphenicol and tetracycline; however, they were sensitive to streptomycin and kanamycin. All strains were able to grow at 35ºC and, except for R17, were tolerant to aluminium (10 mg L-1).